SISTEM INFORMASI INVENTORY VOUCER DAN SIMCARD PADA PT INDOSAT Tbk SEMARANG - Irawan Candra (Semantik, 2011)
Simcard inventory information system and a voucher in PT Indosat Tbk Semarang web-based functions include procurement, warehousing and distribution. The result is expected to produce a system capable of managing inventory simcard and vouchers that can simplify routine recording and reporting inventory data, income, expenditure, search, and facilitate the tracking of evidence inventory process so well controlled.Kata Kunci: information system , inventory, simcard, voucher